Kontiunitas Eksistensi Kerajaan Allah dalam Misi Eklesiologi ditinjau berdasarkan Injil Matius - Sunkudon, Pieter G. O.; Lepa, Royke (STT Bala Keselamatan Palu, 2024)
Abstract: This research aims to explore the continuity of the existence of the Kingdom of God in the ecclesiological mission, especially a review based on the Gospel of Matthew, using Qualitative & Inductive Hermeneutic methods. Through analysis of the Biblical text, this research will highlight the Kingdom of God in the teachings and ministry of Jesus, as well as its correlation with the concept of the church. Apart from that, this research will also examine the use of the term